Low Molecular Weight Heparin (KABI2165) as Thromboprophylaxis in Elective Visceral Surgery - Koller, Matthias; Schoch, Ursula; Buchmann, Peter; Largiadèr, Felix; von Felten, Arthur; Frick, Paul G (Thrombosis and Haemostasis, 1986)
In two randomized double-blind studies perioperative bleeding complications and thromboembolic events were assessed in 189 patients (pts) undergoing elective visceral surgery after subcutaneous administration of a low molecular weight (LMW) heparin fragment (KABI fragment 2165) or unfractionated (UF) heparin. The first study comparing 1 x 7′500 anti-factor Xa IU LMW heparin daily with 2 x 5′000 IU UF heparin was interrupted because of excessive bleeding complications (LMW heparin: 11/23 pts, UF heparin: 2/20 pts, p <0.01). In the second study (146 pts) the dose of LMW heparin was reduced to 1 x 2′500 anti-factor Xa IU. Bleeding complications (LMW heparin: 14.9%, UF heparin: 15.3%) and thromboembolic events (LMW heparin: 2.86%, UF heparin: 2.94%) were equal among the two groups.2′500 anti-factor Xa IU/day of this LMW heparin fragment, corresponding to 15 mg/day, is the lowest dose of a LMW heparin used in a randomized clinical trial and was found to be a safe and efficient regimen in perioperative thrombosis prophylaxis. An advantage of LMW heparin over UF heparin is its once daily administration.
Keywords: Low molecular weight heparin; Bleeding complications; Administration once daily; F Xa-inhibition